Supervisi Pendidikan Sebagai Strategi Peningkatan Profesionalisme Guru - Della Marsya Pratama; Suci Yuniati; Annisah Kurniati; Depriwana Rahmi (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
A major contributor to raising educational standards is the professionalism of teachers. The strategic role of educational supervision in this context is to support and empower teachers in the performance of their professional responsibilities through a methodical and ongoing effort. According to this article, educational supervision is a useful tactic for improving teachers' pedagogical, professional, social, and personal competences. Supervision is a technique for teacher self-development as well as evaluation through needs-based and participative approaches. Supervision can promote a professional work culture that supports ongoing teacher development by putting many forms of supervision into practice, including clinical, academic, administrative, and collaborative supervision. The results demonstrate the beneficial effects of regular and thoughtful supervision on school learning quality. Thus, educational monitoring ought to be incorporated into education-related human resource development policies.